Comparative Evaluation of the Results of Treatment of Acute Adhesive Intestinal Obstruction in Children (Eurasian Medical Research Periodical, 2022)
100 endo-surgical and 100 traditional surgery methods were performed, and it was established that a comparative analysis of laparoscopic and traditional methods of treatment showed that endoscopic adhesion has a significant advantage over traditional laparotomy.